Moveon - physical sensitivity and the psychology of sitting - Low, Ivana Si Wei (2017)
This project explores the relationship between our mind and body while in the act of sitting. Chairs are a big part of our daily lives that not many think about. They provide support for us and we sit on them for long durations not knowing the adverse effects it has on our physical and mental state. Many of us have lost our physical sensitivity towards sitting and end up being passive sitters. Is the solution of a more active sitting experience found in a single ergonomic designed form or something more abstract?